I Don't Care What You Meant: I Heard What You Said - Hickey, Leo (Miscelánea: A Journal of English and American Studies, 1994)
In recent work on interpersonal communication, it is broadly assumed that a sincere Hearer attempts to cooperate with a Speaker in order to interpret the semantic and pragmatic import of what the latter says. However, it sometimes suits the Hearer's purposes better to ignore the Speaker's intentions and seek some other interpretation, so long as it is somehow justified by the literal meaning of the utterance itself. It is suggested that this kind of hostile or uncooperative behaviour is analogical to the Hearer's part to lying on the Speaker's, although its motivation may not always be malicious or negative.